Do communities of practice enhance faculty development? - Abigail, Lum Kai Mun (Health Professions Education, 2016)
The purpose of this systematic literature review was to find out how communities of practice (CoP) work for faculty development, discover if CoP have demonstrated their effectiveness and identify factors that could influence effectiveness of CoP to inform future design and delivery of CoP for faculty development. A systematic literature review was conducted in October 2015 for studies published between 1 January 1991–30 October 2015. To find out if CoP have demonstrated their effectiveness adequately, an overview of study designs, sample and sources of data used in relation to the framework for assessing value in CoP by Wenger et al.1 was done. Findings for factors that could influence CoP׳s effectiveness were written on “Post-it” notes, categorised for themes and sub-themes till saturation through the use of grounded theory approach. 24 articles reviewed. Most studies demonstrated that CoP could make a difference to the educators’ practices through actual application of knowledge, tools and social relationships. Only 1 study2 proved adequately that CoP׳s interventions for faculty development led to actual performance improvement. Factors that could influence CoP׳s effectiveness for faculty development were temporal, personal, key roles played by members in CoP and the environment. CoP provide opportunities for actual application of knowledge, tools and social relationships. More studies are needed to demonstrate if these opportunities for actual application would lead to improved performance in health professions education, through deliberate efforts to design and deliver CoP׳s activities.
Keywords: Communities of practice; Continuing professional development; Effectiveness of communities of practice; Faculty development; Situated learning